Impacts of Touch Screen Size, User Interface Design, and Subtask Boundaries on In-Car Task's Visual Demand and Driver Distraction. Issue 142 (October 2020) - Grahn, Hilkka; Kujala, Tuomo
Highlights: In-car UI design factors' visual distraction potential should be better understood First study on UI features' visual demand while controlling visual demands of driving Automotive-targeted application decreases glance durations and visual distraction Larger screen size has relatively small decreasing impact on glance durations Subtask boundaries enable adjustment of glancing behavior in relation to driving situation Visual demand of a task is not equal to visual distraction ABSTRACT: Visual distraction by secondary in-car tasks is a major contributing factor in traffic incidents. In-car user interface design may mitigate these negative effects but to accomplish this, design factors' visual distraction potential should be better understood. The effects of touch screen size, user interface design, and subtask boundaries on in-car task's visual demand and visual distraction potential were studied in two driving simulator experiments with 48 participants. Multilevel modeling was utilized to control the visual demands of driving and individual differences on in-car glance durations. The 2.5" larger touch screen slightly decreased the in-car glance durations and had a diminishing impact on both visual demand and visual distraction potential of the secondary task. Larger relative impact was discovered concerning user interface design: an automotive-targeted application decreased the visual demand and visual distraction potential of the in-car tasks compared to the use of regular smartphone applications. Also, impact of subtask boundaries was discovered: increase in the preferred number of visual or visual-manual interaction steps during a single in-car glance (e.g., pressing one button vs. typing one word) increased the duration of the in-car glance and its visual distraction potential. The findings also emphasize that even if increasing visual demand of a task – as measured by in-car glance duration or number of glances – may increase its visual distraction potential, these two are not necessarily equal.